Musculoskeletal pain and menopause. Issue 1 (March 2018) - Watt, Fiona E
Musculoskeletal pain, arthralgia and arthritis are all more common in women, and their frequency increases with age and in some appears to be associated with the onset of menopause. The clinical assessment, investigation and management of women presenting with musculoskeletal pain, arthralgia or arthritis at the time of menopause are reviewed. Common causes of arthralgia and arthritis in this population are discussed. The epidemiological and trials evidence for the effects of hormone replacement therapy on musculoskeletal pain and arthritis (primarily from RCTs of HRT for other menopausal symptoms) are discussed. Lastly, the possible underlying aetiological roles of sex hormones including estrogen, and their deficiency, in predisposing to musculoskeletal pain and arthritis are overviewed. Although the association appears strong, a causal link between estrogen deficiency and musculoskeletal pain or different types of arthritis is lacking; there have been few studies specifically within this group of symptomatic patients, and there is much still to understand about musculoskeletal pain and arthritis at the time of the menopause, and about how we might prevent or treat this.